Single Center Experience in the Surgical Management of Primary Hyperparathyroidism - YAVUZ, DİLEK (KOREAN SOC OTORHINOLARYNGOL, 2020)
Objectives. As calcium included as a part of routine laboratory screening early diagnosis of primary hyperparathyroidism (PHPT) has been increased. Surgical resection of parathyroid adenoma or hyperplasia still is the mainstay of the treatment for most PHPT patients. The aim of this study was to evaluate of the surgical outcomes of patients with PHPT that referred to our ENT department of our University Hospital for the last 6 years. Methods. One hundred thirty-seven patients with PHPT who underwent parathyroid surgery in our clinic between October 2011 and January 2018 included in this retrospective study. Data on demographics, clinical findings, past medical history, preoperative laboratory values in 3 months, preoperative localizing imaging studies including ultrasonography (USG) and 99mTc-sestamibi (methoxyisobutyl isonitrile, [MIBIJ) scan, operative findings, postoperative laboratory values, and pathology reports were recorded. MIBI scan and USC; are used as the first-line modalities in our center. Single-photon emission computed tomography was used for challenging situations of re-exploration and ectopic parathyroid pathology Four-dimensional computed tomography scanning is was preferred as the last imaging modality. Focused unilateral neck exploration (FUNE) was performed with intraoperative frozen section analysis as a routine procedure. Bilateral neck exploration (BNE) was used only in re-exploration, ectopic parathyroid, and with high suspicion of multigland disease. Results. Totally 137 patients (female:male, 3:3; mean age, 54.6 +/- 13.2 years) included in the study. Single parathyroid adenoma was found in 108 patients (78.8%). Most common adenoma localization was left inferior parathyroid gland (46.7%). FUNE was performed in 89.8% of the patients and BNE for 10.2% of the patients. Postoperative normocalcemia was reached in 132 patients and permanent hypocalcemia was observed in two patients. Persistence hypercalcemia observed in three patients. Postoperative pathology reports revealed three patients have parathyroid carcinoma. Conclusion. Preoperative imaging modalities is very important in parathyroidectomy surgery. Routine use of preoperative imaging modalities reduced the risk of complications in our clinic.
Keywords: Primary Hyperparathyroidism; parathyroidectomy; Bilateral Neck Exploration; Four-Dimensional Computed Tomography Scanning; PREOPERATIVE LOCALIZATION; PARATHYROIDECTOMY; EXPLORATION; GUIDELINES